Constraints in Utilization and Accessibility of Extension Service Delivery Perceived by KVK Beneficiary Farmers of Chhattisgarh (Indian Journal of Extension Education, 2018)
The present study was conducted purposively in Chhattisgarh state, with a view to evaluate constraints faced by Krishi Vigyan Kendra beneficiary farmers in utilization and accessibility of extension service delivery. Chhattisgarh comprises of three agro-climatic zones, out of that one district were selected randomly from each agro-climatic zones. From each selected districts, 40 KVK beneficiary farmers were selected randomly which constitute a total sample size of 120. A list of constraints were classified into five categories namely Infrastructural, technical, socio-economic, organizational and other constraints measured with the help of a 3 points continuum scale as most serious (3), serious (2) and least serious (1). Data was collected through pretested semi-structured interview schedule. The result showed that lack of resource at village level (2.42), costly inputs/technologies (2.31), lack of education (2.35), lack of timely advice and guidance (2.27) and climatic risk and uncertainty (2.13) were reported with respective total weighted mean scores (TWMS). The finding of the study signify that it is essential to call for attention from government, policy maker, and planners to design effective policy/ strategy that would ensure to measures overcome the constraints faced by the farmers in reaping the benefits of KVK.